2020
DOI: 10.1097/shk.0000000000001545
|View full text |Cite
|
Sign up to set email alerts
|

Does End-Expiratory Occlusion Test Predict Fluid Responsiveness in Mechanically Ventilated Patients? A Systematic Review and Meta-Analysis

Abstract: Background: We performed a systematic review and meta-analysis of studies investigating the end-expiratory occlusion (EEO) test induced changes in cardiac index (CI) and in arterial pressure as predictors of fluid responsiveness in adults receiving mechanical ventilation. Methods: MEDLINE, EMBASE, Cochrane Database, and Chinese database were screened for relevant original and review articles. The meta-analysis determined the pooled sensitivity, specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 46 publications
1
13
2
Order By: Relevance
“…Different clinical settings were also accountable, but we disagreed with Shi et al [ 22 ] who accounted the contradictory results to lung compliance since we found TVC was unaffected by reduced lung compliance. Besides, recent meta-analysis of EEO, the similar theory of heart–lung interaction functional test to TVC, was also proved to be limited in prone position [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different clinical settings were also accountable, but we disagreed with Shi et al [ 22 ] who accounted the contradictory results to lung compliance since we found TVC was unaffected by reduced lung compliance. Besides, recent meta-analysis of EEO, the similar theory of heart–lung interaction functional test to TVC, was also proved to be limited in prone position [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The threshold for SV change for FR has been 5% ( Table 1 ) [ 42 , 58 , 60 , 61 ], and the accuracy of EEOT, regardless of ventilator settings and me-thods of CO (SV) measurement, has been confirmed by a recent meta-analyses [ 20 , 57 , 61 ]. The reliability may be affected when the test was performed in a prone position, as indicated by a previous study [ 61 ].…”
Section: Dynamic Measurements Based On Fluid Challengementioning
confidence: 99%
“…The in terruption of this effect at the end of the expiration phase for at least 12 s [57] results in increased venous return (VR) that results in increased SV; however, other studies indicate a longer expiration phase at 15 s [58,59]. The threshold for SV change for FR has been 5% (Table 1) [42,58,60,61], and the accuracy of EEOT, regardless of ventilator settings and me thods of CO (SV) measurement, has been confirmed by a re cent metaanalyses [20,57,61]. The reliability may be affected when the test was performed in a prone po sition, as indicated by a previous study [61].…”
Section: Dynamic Measurements Based On Fluid Challengementioning
confidence: 99%
“…Messina et al conducted a meta-analyses and systematic review to check the reliability of the EEOT and of the mini-fluid challenge for predicting fluid responsiveness. 67 The areas under the curve (AUC) for EEOT was 0.96, with pooled sensitivity and specificity of 0.86 and 0.91, respectively. They concluded that EEOT and the mini-FC reliably predict fluid responsiveness.…”
Section: R Ecommendations With E Vidence...mentioning
confidence: 99%